Службова кар'єра державного службовця : поняття та особливості - Біла-Тіунова, Любов Романівна; Била-Тиунова, Любовь Романовна; Bila-Tiunova, Ljubov' (My University, 2012)
The article is devoted to the research of a service career of state servant, as a administrative-legal category. Special attention is devoted to the definition of the essence of the term “career» in such sciences as sociology, psychology, personnel management and law. There are analyzed in the article main aspects of the term “state career» (social, legal, organizational, procedural, structural, public-individual) and its specific features (is strategically, is dynamic, is realized in space and time, is inseparably connected with state activity, is a combination of individual and public interests, is determined on final aim — success, is possible in conditions of interaction of state servant and state, is always motivated).
Біла-Тіунова Л. Р. Службова кар'єра державного службовця : поняття та особливості / Л. Р. Біла-Тіунова // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 127-139.
Keywords: кар'єра; службова кар'єра; державний службовець; мотивація; успіх; державна посада; карьера; служебная карьера; государственный служащий; мотивация; успех; государственная должность; career; service career; state servant; motivation; success; state post